A powder metallurgy route to fabricate CNT-reinforced molybdenum-hafnium-carbon composites. (June 2020) - Wei, Yong; Luo, Lai-Ma; Liu, Huai-Bing; Zan, Xiang; Song, Jiu-Peng; Xu, Qiu; Zhu, Xiao-Yong; Wu, Yu-Cheng
Abstract: An efficient powder metallurgy route including wet dispersion, high energy ball milling (HEBM) and spark plasma sintering (SPS) was proposed to fabricate carbon nanotube reinforced molybdenum‑hafnium‑carbon (CNT-reinforced MHC) composites. To improve the dispersion efficiency of carbon nanotubes (CNTs) in the molybdenum (Mo) matrix, acid treatment was used to de-agglomerate CNTs. Carbon nanotube/hafnium hydride (CNT/HfH2 ) powder prepared by wet dispersion and the powder subsequently milled with Mo through HEBM to fabricate MHC composite powder. The results show that this powder metallurgy process improved the dispersion uniformly of HfC and grain size. The strengthening mechanism of dispersion strengthening, grain refinement, lattice distortion and purification of free oxygen improved the relative density, microstructures and mechanical properties of the CNT-reinforced MHC composites. As a result, compared to other control groups and Mo based composites, the 30 h ball milling time of CNT-reinforced MHC composite (30 h composite) exhibits simultaneous enhancement in relative density, mechanical properties and improvement in microstructure. This work provides a feasible way to fabricate high-performance Mo matrix composites. Graphical abstract: Unlabelled Image Highlights: An efficient powder metallurgy utilizing CNT was proposed to fabricate MHC composite. This process improved the dispersion uniformity of HfC and grain size. Simultaneous improvement in microstructure and mechanical properties were achieved in composite.